Equine Osteochondrosis: A controversial disease with multifactorial etiology (Gaceta de Ciencias Veterinarias, 2018)
Osteochondrosis (OC) is an osteoarticular disorder that mainly affects humans, pigs, horses and dogs. Is one of the most common joint diseases of growing horses, belonging to developmental orthopedic diseases complex. It is characterized by an alteration of the endochondral ossification that affects growth of cartilage and the subchondral bone, and is considered the primary phase of damage to joint-epiphyseal complex. Its etiology is reported to be multifactorial and etiological factors most often described are heredity, dietary and endocrine imbalances, rapid growth, trauma and vascular defects of the growth cartilage, but it is incompletely understood, and there is great controversy about the participation and interaction of these factors in appearance of the disease. Osteochondrosis is a disease that causes great economics losses in horse industry, representing an important problem for the sector, hence the great interest in determining its origin.
Keywords: equine; osteochondrosis; growth cartilage; subchondral bone; multifactorial etiology